Does the long-term oral creatine supplementation improve repeated sprint perfromance in elite swimmers? - Shiraki, T.; Nomura, T. (Biomechanics and Medicine in Swimming X, 2006)
This study investigated the effects of high-dose/long-term oral creatine supplementation on repeated sprint swimming performance in elite male swimmers. Twelve subjects, all swimmers, were separated randomly into creatine group (n = 6) and placebo group (n = 6). Swimmers of the creatine group were supplemented creatine (12 g/day) during 8 weeks. Supplementation was performed using double-blind method. Before and at the end of supplementation, 31P-NMR spectroscopy of the triceps muscle of the arm, blood analysis, and intermittent repeated sprint swimming tests were conducted. Eight-week creatine supplementation tended to increase the muscle PCr content (p = 0.055). However, no significant improvement was shown for repeated sprint swimming performance. These results suggest that high-dose/long-term creatine supplementation increased muscle PCr content with no disadvantage to physiological functions in elite male swimmers. However, it was difficult to prove an ergogenic effect on repeated sprint performance in elite male swimmers.